Double-difference adjoint tomography of the crust and uppermost mantle beneath Alaska - Chen, Guoxu (2023)
We perform adjoint waveform tomography to reveal the P-wave velocity structure of the crust and uppermost mantle in Alaska by using common-source double-difference traveltime data. Our underlying forward modeling tool is a 3D seismic-wave solver called SPECFEM3D_GLOBE. We select ∼13,000 high-quality P-wave arrivals from 147 earthquakes recorded by more than 600 stations. The waveforms are filtered between 15 and 8 s and used to generate about 100,000 differential traveltimes via the cross-correlation technique. We invert these common-source differential traveltimes for a P-wave velocity model down to 150 km depth in Alaska. In the upper mantle, a high-velocity zone is imaged along the Aleutian volcanic arc, which represents the Pacific plate subducting beneath the North America plate. On the eastern edge of the subducting Pacific plate, the imaged high-velocity anomaly extends distinctly beyond the Wadati–Benioff zone, indicating an aseismic slab edge. We observe an absence of a low-velocity mantle wedge beneath the Denali Volcanic Gap (DVG) in our tomographic model. This finding suggests that minimal melt accumulation exists beneath the DVG, which may explain the cessation of magmatism there. Our model also reveals a high-velocity anomaly near the Wrangell Volcanic Field (WVF), suggesting the possible existence of the Wrangell slab or the high-velocity slab edge of the Yakutat slab. A potential slab gap shown as a low-velocity body is detected at 95–125 km depth near the WVF, which could act as a channel to transport mantle materials to feed the cluster of volcanoes in the WVF.